High-resolution phylogenetics and phylogeography of human immunodeficiency virus type 1 subtype C epidemic in South America. - Véras, N; Gray, R; Brígido, L; Rodrigues, R; Salemi, M (2011)
Human immunodeficiency virus type 1 subtype C (HIV-1C) represents 30-65% of HIV infections in southern Brazil, and isolated cases of HIV-1C infection have also been reported in Argentina, Uruguay, Paraguay and Venezuela. Phylogenetic studies have suggested that the Brazilian subtype C epidemic was initiated by the introduction of closely related strains. Nevertheless, because of sampling limitations, the point of entry and the timing of subtype C introduction into Brazil, as well as the origin of the founder lineage, remain controversial. The present study investigated the origin, spread and phylogeography of HIV-1C in South America. Phylogenetic analysis showed a well-supported monophyletic clade including all available strains from Brazil, Uruguay and Argentina. Only one lineage from Venezuela was unrelated to the epidemic involving the other three countries. Molecular clock and likelihood mapping analysis showed that HIV-1C introduction in Brazil dated back to the period 1960-1970, much earlier than previously thought, and was followed by a nearly simultaneous star-like outburst of viral lineages, indicating a subsequent rapid spread. Phylogeographic patterns suggested Paraná or Rio Grande do Sul as the possible entrance points of subtype C and an asymmetrical gene flow from Paraná to Sao Paulo, Santa Catarina and Rio Grande do Sul, as well as from Rio Grande do Sul to Sao Paulo fostered by the strong inter-connectivity between population centres in southern Brazil. The study illustrates how coupling phylogeography inference with geographical information system data is critical to understand the origin and dissemination of viral pathogens and potentially predict their future spread.